2020
DOI: 10.1097/icl.0000000000000698
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of In Vitro Wettability of Soft Contact Lenses Using Tear Supplements

Abstract: To evaluate the interaction between tear supplements and soft contact lenses (SCLs), we measured the contact angles (CAs) on the SCLs using commercially available tear supplements. Methods: We used four daily disposable conventional hydrogel lenses (etafilcon A, etafilcon A+ polyvinylpyrrolidone, nelfilcon A, and omafilcon A containing 2-methacryloyloxyethyl phosphorylcholine [MPC]) and four silicone hydrogel lenses (narafilcon A, senofilcon A, delefilcon A, and stenfilcon A). The CAs on the SCLs were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…Higher values of this parameter for silicone hydrogel contact lenses may be related to the bulk content of the Si-rich hydrophobic phase reaching over 30% [70]. Similar studies were carried out by Iwashita et al [71], who made the opposite conclusion that CA values associated with the silicone hydrogel contact lenses were significantly lower than those associated with the hydrogel contact lenses. In addition, storing the contact lenses in HA increased CA values.…”
Section: Discussionmentioning
confidence: 78%
“…Higher values of this parameter for silicone hydrogel contact lenses may be related to the bulk content of the Si-rich hydrophobic phase reaching over 30% [70]. Similar studies were carried out by Iwashita et al [71], who made the opposite conclusion that CA values associated with the silicone hydrogel contact lenses were significantly lower than those associated with the hydrogel contact lenses. In addition, storing the contact lenses in HA increased CA values.…”
Section: Discussionmentioning
confidence: 78%
“… 16 , 29 CA may vary depending upon the SCL material, 16 tear component, 37 and tear supplements. 29 TMH representing the tear volume reduced while wearing the SCL compared to the TMH before wearing the SCL. 38 Chen et al reported that lower the tear volume with SCLs, higher the subjective symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…CA was measured using the sessile drop technique by the CA analyzer (Drop Master DMs-401, Kyowa Interface Science Co., Ltd., Nobitome Niiza, Japan). 29 Five new samples of each type of SCLs were evaluated using saline. After retrieval from the blister pack, the SCLs were carefully grasped at the edge using forceps and were carefully contacted with a cloth (TechniCloth TX604, Texwipe, Kernersville, NC) only at the edge to remove the excess liquid.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to having varying physicochemical properties, wetting agents interact differently with different contact lens materials. Using a modified in vitro method, the wettability of hydrogel and SiHy contact lens materials using a sessile drop composed of either saline or three different artificial tear solutions has been measured [224]. The study found that contact angles were generally lower for hydrogels compared to SiHys and for a lubricant solution containing 2-methacryloyloxyethyl phosphorylcholine compared to another lubricant solution containing HA.…”
Section: Rewetting Dropsmentioning
confidence: 99%